Development of an Efficient Photobioreactor for CO2 Mitigation and Microalgae Biomass Production: Simulation and Optimisation - Naderi, Gita (Curtin University, 2016)
Recently microalgae cultivation has been intensively investigated as a sustainable and eco-friendly approach for CO2 mitigation. Among the effective parameters, the light availability considered as one of the most outstanding limiting factors and an obstacle due to complexity. Light intensity, light period and light distribution inside the culture, as well as their influence on the performance of the photobioreactor in terms of biomass growth, CO2 biofixation and CO2 utilisation efficiency were investigated in this study.